(untitled) (Zamonaviy dunyoda pedagogika va psixologiya, 2022)
In this article, there are basic information on referring to this novel "The Temple of My Familiar," a more detailed analysis of the novel's seconds, Walker's theoretical methods of describing or developing works on femininity. If we take Walker's original definition of the concept as a starting point, after analysis, it should not surprise us that most of the aspects discussed in the four topics and the description of the section is literally irreversible in the novel. Also, in my opinion, the book confirms Walker’s most striking and perhaps most important feature is femininity: her universalist position. It is this attitude that is most important in contrast to basic feminism and African-Americanism.